2017
DOI: 10.1007/s11356-017-8893-9
|View full text |Cite
|
Sign up to set email alerts
|

Airborne trace elements near a petrochemical industrial complex in Thailand assessed by the lichen Parmotrema tinctorum (Despr. ex Nyl.) Hale

Abstract: Several trace elements discharged by the petrochemical industry are toxic to humans and the ecosystem. In this study, we assessed airborne trace elements in the vicinity of the Map Ta Phut petrochemical industrial complex in Thailand by transplanting the lichen Parmotrema tinctorum to eight industrial, two rural, and one clean air sites between October 2013 and June 2014. After 242 days, the concentrations of As, Cd, Co, Cr, Cu, Hg, Mo, Ni, Pb, Sb, Ti, V, and Zn in lichens at most industrial sites were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 67 publications
0
13
0
1
Order By: Relevance
“…Owing to the very slow growth rate of lichens, different parts of radially growing foliose lichen represent different ages of lichen thallus. Assuming that the growth rate of P. tinctorum is approximately 2 cm/year [ 53 ], the center, middle, and margin parts of the sample (thallus 3, for example) represent thalli of 6.25 (±1.25), 3.75 (±1.25), and 1.25 (±1.25) years old, respectively ( Figure 1 a). The ELF species of Mollisia sp., Coniochaeta boothii , and Muscodor fengyangensis , were uniquely isolated from the young marginal parts of the lichen thallus ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the very slow growth rate of lichens, different parts of radially growing foliose lichen represent different ages of lichen thallus. Assuming that the growth rate of P. tinctorum is approximately 2 cm/year [ 53 ], the center, middle, and margin parts of the sample (thallus 3, for example) represent thalli of 6.25 (±1.25), 3.75 (±1.25), and 1.25 (±1.25) years old, respectively ( Figure 1 a). The ELF species of Mollisia sp., Coniochaeta boothii , and Muscodor fengyangensis , were uniquely isolated from the young marginal parts of the lichen thallus ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that high quantities of metals in lichens in urban and/or industrial areas were associated to the local traffic density (Boonpeng et al, 2017b;Guidotti et al, 2009;Koz et al, 2010;Olowoyo et al, 2011;Sorbo et al, 2008). A number of studies have been carried out along highways in rural and natural areas to clarify and assess the impact of road traffic on atmospheric metal pollution (Liu et al, 2018;Yemets et al, 2014;Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of each metal from each sampling site was compared with its background concentration to determine the variation from its baseline concentration. The background concentrations were obtained from the same lichen species (P. tinctorum), which were collected on various tree species in all seasons at KYNP (Boonpeng, 2016;Boonpeng et al, 2017b). The results were subsequently interpreted using bioaccumulation ratios (B ratio) (B ratio=mean concentration of an analyzed metal in a sampling site divided by mean background concentration of that metal): ≤1.0=absence of bioaccumulation, >1.0-2.1=low bioaccumulation, >2.1-3.4=moderate bioaccumulation, >3.4-4.9=high bioaccumulation, and >4.9=severe bioaccumulation (Cecconi et al, 2019).…”
Section: Data Interpretationmentioning
confidence: 99%
See 2 more Smart Citations